Impact of cardiopulmonary bypass on peripheral tissue metabolism and microvascular blood flow - Manďák, Jiří; Pojar, Marek; Cibiček, Norbert; Lonský, Vladimír; Palička, Vladimír; Kakrdová, Dana; Nedvídková, Jara; Kubíček, Jaroslav; Živný, Pavel (Perfusion, 2008)
The aim of this study was to monitor and compare the changes in metabolism and blood flow in the skeletal muscles during cardiac operations performed with cardiopulmonary bypass (CPB) and operations without CPB (off-pump) by means of interstitial microdialysis (Figure 1). Surgical revascularization, coronary artery bypass grafting (CABG), was performed in 40 patients randomized to two groups. Twenty patients (On-Pump Group) were operated on using CPB, 20 patients (Off-Pump Group) were operated on without CPB. Interstitial microdialysis was performed by 2 probes of a CMA 60 (CMA Microdialysis AB, Solna, Sweden) inserted into the patient's deltoid muscle. Microdialysis measurements were performed at 30-minute intervals. Glucose, lactate, pyruvate and glycerol as markers of basic metabolism and tissue perfusion were measured in samples from the first probe, using a CMA 600 Analyzer (CMA Microdialysis AB). Blood flow through the interstitium was monitored by means of dynamic microdialysis of ethanol as a flow-marker in the dialysates taken from the second probe (ethanol dilution technique). Results in both the groups were statistically processed and compared. Both the groups were similar in respect of preoperative characteristics. Dynamic changes of interstitial concentrations of the measured analytes were found in both the patient groups (on-pump vs. off-pump) during the operation. There was no significant difference in dialysate concentrations of glucose and lactate between the groups. Significant differences were detected in pyruvate and glycerol interstitial concentrations, lactate/pyruvate ratio and lactate/glucose ratio between the on-pump vs. off-pump patients. In the Off-Pump Group, pyruvate concentrations were higher and the values of concentrations of glycerol lower. The lactate/pyruvate ratio and the lactate/glucose ratio, indicating the aerobic and anaerobic tissue metabolism status, were lower in the Off-Pump Group. There was no significant difference in dialysate concentrations of ethanol as a flow-marker during the surgery in either of the groups. There was no statistically significant difference between the groups (On-Pump Group vs. Off-Pump Group) comparing the postoperative clinical outcome (ICU stay, ventilation duration, length of hospital stay). The dynamic changes in the interstitial concentrations of the glucose, glycerol, pyruvate and lactate were found in both the groups of patients (On-Pump Group and Off-Pump Group), but there was no difference in local blood flow when the ethanol dilution technique was used. These results showed significantly higher aerobic metabolic activity of the peripheral tissue of patients in the Off-Pump Group vs. the On-Pump Group during the course of cardiac revascularization surgery. Results suggest that extracorporeal circulation, cardiopulmonary bypass, compromises peripheral tissue (skeletal muscles) energy metabolism. These changes have no impact on the postoperative clinical outcome; no significant difference between the groups was found.
Keywords: kosterní svaly; Female; Regional Blood Flow; Cardiac Surgical Procedures; Postoperative Period; peroperační doba; koronární bypass bez mimotělního oběhu; ženské pohlaví; kardiopulmonální bypass; mimotělní oběh; lidé; Coronary Artery Bypass, Off-Pump; kardiochirurgické výkony; Microdialysis; Muscle, Skeletal; mikrodialýza; Cardiopulmonary Bypass; pooperační období; prospektivní studie; Male; Aged; Prospective Studies; předoperační péče; regionální krevní průtok; Preoperative Care; senioři; mužské pohlaví; Extracorporeal Circulation; Intraoperative Period; Humans